2018
DOI: 10.1111/mmi.14097
|View full text |Cite
|
Sign up to set email alerts
|

G1 and S phase arrest in Candida albicans induces filamentous growth via distinct mechanisms

Abstract: Candida albicans is an opportunistic fungal pathogen. In immunocompromised individuals, it can cause bloodstream infections with high mortality rates. The ability to switch between yeast and hyphal morphologies is a critical virulence factor of C. albicans. In response to diverse environmental cues, several signaling pathways are activated resulting in filamentous growth. Interestingly, cell cycle arrest can also trigger filamentous growth although the pathways involved are not well-understood. Here, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…This process involves ϳ700 genes for pseudohypha formation in S. cerevisiae (27,28) and more than 2,000 genes in C. albicans filamentous growth (29). However, mutation of key genes regulating filamentous growth, such as HGC1, UME6, FLO8, TEC1, NRG1, CPH1 (STE12 in S. cerevisiae), or EFG1, does not affect HU-induced pseudohypha formation (19,49,50). Therefore, pseudohyphal growth upon genotoxic stress apparently involves, at least partially, different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves ϳ700 genes for pseudohypha formation in S. cerevisiae (27,28) and more than 2,000 genes in C. albicans filamentous growth (29). However, mutation of key genes regulating filamentous growth, such as HGC1, UME6, FLO8, TEC1, NRG1, CPH1 (STE12 in S. cerevisiae), or EFG1, does not affect HU-induced pseudohypha formation (19,49,50). Therefore, pseudohyphal growth upon genotoxic stress apparently involves, at least partially, different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, mutation of CLB2, CDC28, and CDC5 triggers constitutive pseudohyphal growth in yeasts (49,70,71). Furthermore, the cAMP and MAPK pathways have been implicated in pseudohyphal growth in response to genotoxic stress via downstream regulators (18,42,50,72). A plausible model for C. auris is depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pathways for hyphal induction upon interference with the cell cycle progression include the transcription factor Ume6 and the Cdc28 cyclin Hgc1 in the case of the depletion of Cdc5 or Cln3, but not for hydroxyurea-induced filamentous growth. The latter, however, still required the Ras-cAMP pathway activity [133,134]. HSG expression induced by diminished CAK1 expression was surprisingly resistant to the deletion of TFs that are normally essential for hyphal growth under many conditions, in particular, Ume6 and Brg1.…”
Section: Regulation Of Hyphal Morphogenesis and Hsg Expression By mentioning
confidence: 99%
“…Also, an investigation into the cAMP requirement for hyphal morphogenesis showed that basal levels of cAMP are sufficient for hyphal formation in response to N -acetylglucosamine (GlcNAc), suggesting that cAMP-independent signals are also important for hyphal induction 47 . Both G 1 and S phase arrest can induce filamentous growth and this has been shown to require the cAMP/PKA pathway 48 .…”
Section: Hyphal Growth Signalingmentioning
confidence: 99%